2003
DOI: 10.1161/01.cir.0000079223.47421.78
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Prevention of Distal Embolization During Primary Angioplasty

Abstract: Background-Effective myocardial reperfusion after primary percutaneous coronary intervention (PCI) may be limited by distal embolization. We tested the safety, feasibility, and efficacy of the FilterWire-Ex (FW), a distal embolic protection device, as an adjunct to primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 42 publications
2
96
0
4
Order By: Relevance
“…Although the use of GuardWire during primary PCI in AMI does not improve microvascular flow or function, reduce infarct size, or enhance long-term eventfree survival, 82,83 most studies confirm that distal protection devices may prevent many unfavourable events by limiting embolization and improving outcomes. Distal embolization may be successfully minimized by using the AngioGuard Emboli Capture Guidewire (Cordis).…”
Section: Distal Embolization Prevention and Intra-aortic Balloon Counmentioning
confidence: 99%
“…Although the use of GuardWire during primary PCI in AMI does not improve microvascular flow or function, reduce infarct size, or enhance long-term eventfree survival, 82,83 most studies confirm that distal protection devices may prevent many unfavourable events by limiting embolization and improving outcomes. Distal embolization may be successfully minimized by using the AngioGuard Emboli Capture Guidewire (Cordis).…”
Section: Distal Embolization Prevention and Intra-aortic Balloon Counmentioning
confidence: 99%
“…Moreover, another report demonstrated that distal protection during PCI effectively retrieved the embolic debris and preserved the index of microcirculatory resistance in patients with an acute anterior STEMI [14]. Embolic protection devices are designed to be able to retrieve atherothrombotic debris and prevent its distal embolisation, but their effect on clinical outcomes has not been established, except for saphenous vein bypass grafts [6,7,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Distal embolization of thrombus during balloon inflation or stent deployment carries an increased risk of poor clinical outcomes; [8][9][10][11][12] in a recent study, it was associated with an 8-fold increase in 5-year mortality.…”
Section: Discussionmentioning
confidence: 99%